PENGARUH PARTISIPASI PENGANGGARAN, KOMITMEN ORGANISASI, DAN KETIDAKPASTIAN LINGKUNGAN PADA SENJANGAN ANGGARAN - Nitiari, Ni Luh Nyoman; Yadnyana, Ketut (E-Jurnal Akuntansi, 2015)
Budgetary slack reflects the difference between the amount of the company's best estimate of the budget drawn up by managers to protect themselves from the risk of not achieving budget targets by means of a low budgeted revenues and budgeted costs are high. This study aimed to clarify the effect of budgetary participation and organizational commitment on the slack with environmental uncertainty as a moderating. The study sample consisted of 19 three-star hotels and above in the village of Ubud. There is a positive effect of participation on budgetary slack budgets. Negative influence of organizational commitment on budgetary slack, as well as environmental uncertainty moderates the relationship budgetary participation and organizational commitment on budgetary slack.
Keywords: budgetary participation, organization commitment, environmental uncertainty, budgetary slack